2020
DOI: 10.1017/s1366728920000590
|View full text |Cite
|
Sign up to set email alerts
|

Language control in bilingual production: Insights from error rate and error type in sentence production

Abstract: Most research showing that cognates are named faster than non-cognates has focused on isolated word production which might not realistically reflect cognitive demands in sentence production. Here, we explored whether cognates elicit interference by examining error rates during sentence production, and how this interference is resolved by language control mechanisms. Twenty highly proficient Spanish–English bilinguals described visual scenes with sentence structures ‘NP1-verb-NP2’ (NP = noun-phrase). Half the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 80 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…But, importantly, they mixed identical and high orthographic similarity items and found that very high similarity words (including identical items) were produced faster than high orthographic similarity items, but that phonological dissimilarity hindered performance. Although Schwartz and colleagues observed facilitation in this production task, others have found inhibition for cognates in production, depending on task difficulty 41 . Therefore, this contrast with our results might be due to differences in the task (production versus perception) or it might relate to task difficulty.…”
Section: Discussionmentioning
confidence: 65%
“…But, importantly, they mixed identical and high orthographic similarity items and found that very high similarity words (including identical items) were produced faster than high orthographic similarity items, but that phonological dissimilarity hindered performance. Although Schwartz and colleagues observed facilitation in this production task, others have found inhibition for cognates in production, depending on task difficulty 41 . Therefore, this contrast with our results might be due to differences in the task (production versus perception) or it might relate to task difficulty.…”
Section: Discussionmentioning
confidence: 65%
“…But, importantly, they mixed identical and high orthographic similarity items and found that very high similarity words (including identical items) were produced faster than high orthographic similarity items, but that phonological dissimilarity hindered performance. Although Schwartz and colleagues observed facilitation in this production task, others have found inhibition for cognates in production, depending on task di culty 39 . Therefore, this contrast with our results might be due to differences in the task (production versus perception) or it might relate to task di culty.…”
Section: Discussionmentioning
confidence: 70%
“…Because the effect was different for very similar and more dissimilar cognates, the effect of cognate status in the total duration for the written group may no longer be visible in the main analysis. The effect of orthographic similarity on total duration in the typing of cognates suggests that when there is limited orthographic overlap between cognates, there is cognate interference at the sub-lexical level (see also Martin & Nozari, 2020). One important difference between our study and the one conducted by Muscalu and Smiley (2019) is the type of task that was used (i.e., picture naming vs. translation, respectively).…”
Section: Discussionmentioning
confidence: 81%
“…As a consequence, one would expect more cross-lingual activation in the former type of task compared to the latter. However, even in a monolingual sentence context, cognate interference effects can be observed when the processing demands are increased (Martin & Nozari, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation